THE ROLE OF CONVENIENCE, COMPATIBILITY AND MEDIA RICHNESS IN ACCEPTING MOBILE WEB IN MALAYSIA - L. Thaneshan; Fadhilah Mat Yamin; Siti Norezam Othman, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
Our lifestyle has changed and keeps changing with emerging software and hardware technologies. In the same way, mobile devices are changing the way people accessing the Internet. More users have changed from using desktop computers to mobile devices. A mobile device such as smartphones and tablets are widely used devices in accessing the Internet all over the world. From an early investigation, it is found that although mobile devices are highly flexible, accessible, and convenient, their usage to access websites is still average. The objective of this study is to conceptualize the factors that drive users to access websites through mobile devices. This study presents the scenario and the current situation of mobile web usage among mobile device users. It further critically discusses the role of three constructs namely, convenience, compatibility, and media richness in explaining the user’s intention to use the mobile web. The study adopts the Technology Acceptance Model (TAM) to understand what factors affect usage intention of the mobile web, an important topic for current and future research. The limitations lie in the depth of investigation where the empirical investigation should be conducted in future studies to prove the findings of this conceptual study. This study aims to explain the factors that will influence the intention to access mobile websites. Determining those factors will help web designers to develop mobile web pages that will be preferred by its users. Improving user’s experience of accessing the web through mobile devices will enable web service providers to offer web services more effectively that will satisfy the needs of the users.